An ancient and a recent colonization of islands by an Australian sap‐feeding insect. (10th August 2018) - Fromont, Caroline; Rymer, Paul D.; Riegler, Markus; Cook, James M.
Abstract: Aim: To assess the genetic structure, biogeography, and the potential for speciation, of a highly host‐specific insect pest with mainland and island populations. Location: East coast of Australia, Lord Howe Island (LHI), and New Zealand. Methods: We focussed on Mycopsylla fici, a plant sap‐feeding insect host‐specific to the fig tree Ficus macrophylla . We genotyped 152 insects from across the natural and extended host plant range at 14 microsatellite loci and analysed the data using standard population genetics statistics, Discriminant Analysis of Principal Components, genetic autocorrelation, and two Bayesian clustering approaches. Results: Genetic analyses revealed that the northeastern Australian mainland population (Brisbane) is the centre of genetic diversity. Northeastern and southeastern (Sydney) mainland populations are genetically differentiated and interconnected in a stepping‐stone pattern. The LHI population is the most distinct genetically and Bayesian estimates indicated that the most recent colonization occurred c . 2, 000‐17, 500 years ago from a northeastern mainland origin. In contrast, the New Zealand population is little differentiated from the Sydney population and probably diverged by colonization within the past 200 years. Main conclusions: The strong differentiation in nuclear microsatellites mirrors previous evidence for divergence of the LHI population from both mtDNA and endosymbiont DNA. The LHI population may be undergoing speciation from the mainland populations, with an oceanic barrier to gene flow. In contrast, the geographically isolated population in Auckland represents a far more recent colonization reflecting the contemporary naturalization of the plant host in New Zealand.